Biochemical characterisation supports a central role for Oep80 from Arabidopsis thaliana in chloroplastic β-barrel protein assembly - Rhiannon J. Durant; R. Paul Jarvis; Jani R. Bolla (Communications Biology)
Abstract The outer membranes of Gram-negative bacteria and endosymbiotic organelles mitochondria and chloroplasts contain β-barrel proteins essential for transporting metabolites, ions and proteins, as well as regulatory functions. While the assembly mechanisms of these proteins are well-studied in bacteria and mitochondria, they remain poorly understood in chloroplasts due to challenges in producing sufficient quantities of relevant plant proteins for structural and biochemical analyses. Here, we show that Oep80, the presumed core component of the chloroplastic β-barrel assembly machinery, can be overexpressed in bacteria and refolded in large quantities. While the soluble POTRA domain caused the heterologous protein to aggregate, we found that the isolated β-barrel membrane domain (Oep80β) is very stable and refolds well. Using native mass spectrometry, we further show that purified Oep80β binds predicted β-signals found in several substrate β-barrel proteins in an anti-parallel manner. Overall, our findings support a central role for Oep80 in chloroplast β-barrel biogenesis. They provide evidence that the chloroplastic β-barrel assembly machinery uses a β-signal to recognise its substrates, suggesting mechanistic parallels with the BAM and SAM complexes of Gram-negative bacteria and mitochondria, respectively.